THE INFLUENCE OF AUDIT COMMITTEE AND INTERNAL AUDITOR TOWARD THE PREVENTION OF FRAUD (A SURVEY IN SOES OF INDONESIA) - Angrita Denziana (International Conference On Law, Business and Governance (ICon-LBG), 2016)
The weakness of corporate governance is often called as the cause of some frauds and accounting scandals that were uncovered recently. It requires information quality, and freefromdistortion. Some cases both nationally and internationally indicate the occurrence of irregularitiesin financial reportingdue tothe weakness of the company's internalcontrol system, and theaudit committee has notfunctioned optimally. The audit committee has the responsibility to supervise matters that potentially contain risks in the internal controlling system and to monitor the supervision process conducted by internal auditor, to conduct examination and assessment on sufficiency and effectiveness of internal controlling system. The results show that audit committee optimalization must having experience as auditor in public accountant office and the internal auditor must be improved through quality of internal auditor responsibility in prevention of fraud.